2019
DOI: 10.1194/jlr.m092494
|View full text |Cite
|
Sign up to set email alerts
|

AdipoR1 and AdipoR2 maintain membrane fluidity in most human cell types and independently of adiponectin

Abstract: The FA composition of phospholipids must be tightly regulated to maintain optimal cell membrane properties and compensate for a highly variable supply of dietary FAs. Previous studies have shown that AdipoR2 and its homologue PAQR-2 are important regulators of phospholipid FA composition in HEK293 cells and Caenorhabditiselegans, respectively. Here we show that both AdipoR1 and AdipoR2 are essential for sustaining desaturase expression and high levels of unsaturated FAs in membrane phospholipids of many human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 51 publications
10
78
0
Order By: Relevance
“…In either case, it is interesting to test whether this relationship is conserved between the human AdipoR1 and AdipoR2. For this purpose, we turned to HEK293 cells where the AdipoR1 and AdipoR2 proteins act as functional homologs of PAQR-2 and are required to prevent membrane rigidification when the cells are cultivated in the presence of palmitic acid [ 13 16 , 35 ]. Here, we found that overexpression of either AdipoR1 or AdipoR2 in HEK293 cells is sufficient to prevent membrane rigidification in HEK293 cells challenged with 400 μM palmitic acid ( Fig 5A–5E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In either case, it is interesting to test whether this relationship is conserved between the human AdipoR1 and AdipoR2. For this purpose, we turned to HEK293 cells where the AdipoR1 and AdipoR2 proteins act as functional homologs of PAQR-2 and are required to prevent membrane rigidification when the cells are cultivated in the presence of palmitic acid [ 13 16 , 35 ]. Here, we found that overexpression of either AdipoR1 or AdipoR2 in HEK293 cells is sufficient to prevent membrane rigidification in HEK293 cells challenged with 400 μM palmitic acid ( Fig 5A–5E ).…”
Section: Resultsmentioning
confidence: 99%
“…In eukaryotes, the SREBPs are regulated by the availability of specific lipids such as cholesterol in the ER membrane [8], PCYT1A is activated by association with packing defects in the inner nuclear membrane [9][10][11] and IRE1 is activated by multimerization in response to membrane thickening in the ER [1,12]. Recently we identified a novel regulator of membrane homeostasis in animal cells, namely the PAQR-2/IGLR-2 complex in the nematode C. elegans [13][14][15][16][17][18]. The present work helps define the structure-functional basis of fluidity sensing by this complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] A recent study showed that both adiponectin receptors are involved in regulating cell membrane fluidity in cancer cells. [7] There are two main adiponectin receptors, adiponectin receptor-1 (AdipoR1) and adiponectin receptor-2 (AdipoR2), that have been identified and their expression has been reported in numerous tissues, such as the endometrium, brain and breast tissues obtained from both in humans and animals. [3,[6][7][8][9][10][11] On the other hand, both of adiponectin receptors' expression has also been reported in cancer cell lines and tissues, including breast cancer and endometrial cancer, in which expression of AdipoR1 was shown to be higher compared to that of AdipoR2.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][12][13][14] For example, adiponectin receptors mRNA expression levels were shown in the human mammary tumor, pancreatic, lung and endometrial cell lines. [7][8][9][11][12][13][14] It was reported that adiponectin functions through its receptors via modification of inflammatory signaling molecules, including Erk1/2, Akt, TNFa, IL-1b, NFkB, IL6, IL-8 and MCP1. [14] Another main target for adiponectin protein is liver tissue where it is survival and apoptotic effects were observed in hepatic cells.…”
Section: Introductionmentioning
confidence: 99%